2016
DOI: 10.2196/mhealth.4455
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions of ¡Protéjase!: An Intervention Designed to Increase Protective Equipment Use Among Mexican Immigrant and Mexican American Farmworkers

Abstract: BackgroundFarmworkers’ exposures to pesticides are reduced when they wear personal protective equipment (PPE), and mobile health (mHealth) platforms can potentially deliver information to farmworkers to help promote PPE use. However, little is known about the feasibility of using mHealth platforms to promote farmworkers’ use of PPE.ObjectiveThe objective of the study was to describe the development and feasibility-testing of Protect Yourself! (¡Protéjase!), an intervention designed to increase PPE use. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…These results suggest several generalizations about getting information about health programs to Latino farmworkers that reflect past farmworkers research and programs. 11,17 Health care providers, including hospitals, clinics, doctors, and nurses, are the preferred source of health information. Information from these sources is trusted by most farmworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest several generalizations about getting information about health programs to Latino farmworkers that reflect past farmworkers research and programs. 11,17 Health care providers, including hospitals, clinics, doctors, and nurses, are the preferred source of health information. Information from these sources is trusted by most farmworkers.…”
Section: Discussionmentioning
confidence: 99%
“…Price et al 8 and Sandberg et al 9 indicated that a large and growing number of farmworkers have smart phones. Snipes et al 11 reported a willingness among farmworkers to use mobile devices to receive health information (specific occupational safety information) and provide data through these devices. Grzywacz et al 21 found that other Latino workers (construction workers) would use mobile devices to provide daily diary research data.…”
Section: Discussionmentioning
confidence: 99%
“…We provided participants with three PPE items (i.e., gloves, long-sleeved shirts, and safety glasses) that had been user-tested for functionality and comfort in a previous study as part of the ¡Protejase! study (Snipes et al, 2016). To model an environment in which PPE is recommended but not provided (i.e., workers must provide PPE themselves), we did not provide long pants, boots, and head coverings.…”
Section: Methodsmentioning
confidence: 99%
“…Snipes et al [43,44] published two studies exploring the potential for mHealth interventions to increase the use of personal protective equipment (PPE) among Mexican immigrant and Mexican American farmworkers. The ¡Protéjase!…”
Section: Farmworker Safetymentioning
confidence: 99%
“…A total of 55 farmworkers participated in the ¡Protéjase! mHealth program; 75% of participants completed the program with few noting difficulties in understanding the messages disseminated [44]. Individualized messages were perceived as helpful when they communicated health risks.…”
Section: Farmworker Safetymentioning
confidence: 99%